The Implementation of the Project Based Learning (PjBL) Model in the Era of Independent Learning in Indonesian Language and Literature Development Courses - Sutarini; Dalmi Iskandar; Rahmat Kartolo; Putri Juwita (International Journal of Educational Research Excellence (IJERE), 2023)
The aim of this research is to determine the implementation of the PjBL model in the era of independent learning in the Indonesian Language and Literature Development course. The PjBL model used focuses on product creation and involves students directly in the learning process. This research uses a qualitative descriptive research method. This research was carried out in the even semester of FY 2022-2023. The subjects in this research were 24 semester 6-V students of PGSD UMN Al Washliyah who were taking the Indonesian Language and Literature Development course. The data collection instruments used were observation sheets, questionnaires and student project assignments. The research results show that 91.6 % of the PjBL models used by lecturers during the teaching and learning process have succeeded in making students active, creative and innovative in understanding the material and producing products. This can also be seen from the results of the learning products of the Indonesian Language and Literature Development course, namely that students were able to produce an Anthology of Children's Stories which can be used as a medium or learning resource for Indonesian language subjects in elementary schools.